AKTIVITAS DARI KUERSETIN SEBAGAI AGEN PENCERAH KULIT SECARA IN SILICO - Adnyani, K. D.; Lestari, L. W. E.; Prabowo, H.; Siaka, P. A. I. A.; Laksmiani, N. P. L. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.2 Juli 2019DO - 10.24843/JCHEM.2019.v13.i02.p14, 2019)
Increasing melanogenesis process causes excessive melanin synthesis resulting in darkening of the skin color. The melanogenesis process requires mealnogenesis enzymes, one of which is tyrosinase-related protein 1. One of the flavonoid compounds that has the potential as a skin lightening agent is quercetin. The antioxidant activity of quercetin plays a very important role in antimelanogenesis. This study aims to determine the affinity and molecular mechanism of quercetin on the target protein tyrosinase-related protein 1 using in silico molecular docking method. Molecular docking is carried out through stages including optimization of the structure of quercetin compounds, preparation of the target protein tyrosinase-related protein 1, validation of the molecular docking method, and docking of quercetin on the tyrosinase-related protein 1. Docking of quercetin with tyrosinase-related protein 1 produces binding energy values of -7.81 kcal/mol, while docking of native ligand with tyrosinase-related protein 1 produces binding energy values of -5.39 kcal/mol. Quercetin has a strong affinity for tyrosinase-related protein 1 which is indicated by the binding energy from the docking results. Quercetin has activity as a skin whitening agent with in silico test with molecular mechanisms through inhibition of the activity of tyrosinase-related protein 1 enzyme.  Keywords : skin whitening agent, in silico, quercetin, tyrosinase-related protein 1